Efecto de un service desk en la gestión de incidentes de tecnologías de información en la Universidad Nacional de la Amazonía Peruana, Iquitos - 2020 - Pita Astengo, Luis Honorato (2022)
The National University of the Peruvian Amazon (UNAP) has a computer park of 1,100 computers and peripherals, of varying degrees of obsolescence; which are used by a similar number of teaching and administrative staff, many of they with limited computer knowledge and dispersed in various locations in the city of Iquitos and periphery; the Central Office of Informatics (OCEIN), It’s the unit in charge of solving the computer incidents that said personnel report; Unfortunately, this service lacked formal procedures, suitable tools and benchmarks, that allow adequate control and defined goals, affecting its quality and therefore, generating discomfort and dissatisfaction in users. That is why this thesis proposes, after to identify the status of IT Incident Manage-ment, implement a Service Desk under ITIL v3.0 guidelines, in order to im-prove the Incident Management service provided by the aforementioned of-fice. To measure if this implementation has achieved what was proposed, on a sample of 202 incident reports, five Key Performance Indicators (KPIs) have been compared, in addition to conducting a perception and satisfaction survey that the user has for the service provided. It has been possible to verify by means of a Chi Square test of homogeneity, that the new Service Desk has exceeded the minimum improvement rates that were established for the five proposed KPIs; also, has significantly improve the expectations and sat-isfaction rates expressed by users for the service provided by the IT area. In this research work, it is concluded that it has been possible to demonstrate the General Hypothesis: The development of a Service Desk improves IT Incident Management into UNAP.